2016
DOI: 10.1371/journal.pone.0157244
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of OsSAP16 Regulates Photosynthesis and the Expression of a Broad Range of Stress Response Genes in Rice (Oryza sativa L.)

Abstract: This study set out to identify and characterize transcription factors regulating photosynthesis in rice. Screening populations of rice T-DNA activation lines led to the identification of a T-DNA mutant with an increase in intrinsic water use efficiency (iWUE) under well-watered conditions. Flanking sequence analysis showed that the T-DNA construct was located upstream of LOC_Os07g38240 (OsSAP16) encoding for a stress-associated protein (SAP). A second mutant identified with activation in the same gene exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 81 publications
1
16
0
Order By: Relevance
“…In particular, the higher A observed supported the growth of Eustoma leaves from our results [28]. It is well established that g s correlates with the A [62] and a lower E is also related to a reduction in g s [63]. The higher E under the B and W LEDs led to an increase in fresh biomass and a change in leaf shape compared with the R LEDs at higher PPFDs (Figure 1(A4),C; Figure 2C).…”
Section: Discussionsupporting
confidence: 87%
“…In particular, the higher A observed supported the growth of Eustoma leaves from our results [28]. It is well established that g s correlates with the A [62] and a lower E is also related to a reduction in g s [63]. The higher E under the B and W LEDs led to an increase in fresh biomass and a change in leaf shape compared with the R LEDs at higher PPFDs (Figure 1(A4),C; Figure 2C).…”
Section: Discussionsupporting
confidence: 87%
“…Among them, OsSAP16 showed a 1 bp difference in the promoter region between IR36 and Weiguo and was significantly associated with the salt-tolerant phenotype. This gene encoded a C2H2-type zinc finger protein and would be induced under drought stress (Wang et al 2016). Furthermore, according to the transcriptome analysis and qRT-PCR results, the candidate gene OsSAP16 was significantly down-regulated after salt stress in IR vs. TIR (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, Os07g0569700 was considered as the most possible functional gene underlying qRSL7. The candidate gene Os07g0569700 has been studied and named as OsSAP16 in a prior study (Wang et al 2016). This gene encodes a stress-associated protein and its expression has been shown to increase under drought stress.…”
Section: Identification Of Candidate Genes Responsible For Salt Tolermentioning
confidence: 99%
“…Overexpression of OsSAP16 can regulate the expression of a set of stress-associated genes, including pathogenesis-related (PR) proteins, signaling proteins, secondary metabolism proteins, MYB transcription factor, and peroxidases (Wang et al 2016). We found that the amino acid sequence of OsSAP16 showed the highest homology with TaSAP17 and interestingly, the overexpression of TaSAP17-D upregulated a broad range of stress responsive genes.…”
Section: Zat10mentioning
confidence: 93%